PROGESTERONE PROFILE IN POSTPARTUM LACTATING ONGOLE (ZEBU) COWS - NAIDU, G VENKATA; RAO, A SESHA GIRI; RAO, K BABU (The Indian Journal of Animal Reproduction, 2010)
Serum progesterone (P 4) concentrations were estimated and correlated with postpartum ovarian activity in 6 lactating Ongole cows. The P4concentration was low initially (0.33 to 1.13 ng / ml), with a gradual increase up to day 25 (1.13 to 1.85 ng / ml) and thereafter the concentration was associated with ovarian activity in cyclic cows (1.05 to 0.75 ng / ml). In an acyclicco’<"continuously low progesterone levels were observed. During standing estrus P 4 levels varied significantly (P> 0.05) with an increase up to day 17 of the cycle.